Red-emitting Al2O3:Eu3+ Phosphor Powders Featuring Sheet Morphology for the Application of Fingerprint Revealing - Maria Fernanda IBARRA; David Alejandro CHÁVEZ CAMPOS; Alejandro NÚÑEZ VILCHIS; Maria Guadalupe GODINA CUBILLO; Jose Luis FRAGA ALMANZA; Jorge OLIVA UC; Carlos Eduardo RODRIGUEZ GARCIA (Medžiagotyra)
In this work, Al2O3:xEu3+ red phosphor powders were produced by the combustion synthesis technique with different x molar percentage concentrations of doping of x = 1.5, 3.0, 5.0, and 7.0 mol% of Eu. X-ray diffraction analysis demonstrated that the powders present the Al2O3 crystalline phase. Scanning electron microscopy discovered a sheet-like morphology in the Al2O3:xEu3+ phosphor samples. The sheet particle sizes are in the range of 40 – 280 mm and with an average thickness of 4.8 mm. Photoluminescence measurements of the samples under 254 nm excitation, showed two main red emission peaks at 615 nm and 700 nm attributed to Eu3+ luminescent transitions, 5D0-7F2, 5D0-7F4, respectively. The Al2O3:xEu3+ red phosphors were applied for fingerprint revealing application on different surfaces and in crime scenes. The fingerprints were successfully revealed on steel, plastic, and ceramic surfaces, and photographs of the revealed fingerprints were taken. Several fingerprint features, such as short ridges, eyes, bifurcations, cores, and right loop elements, were clearly detected and sharply defined in the photographs. Therefore, the Al2O3:xEu3+ red phosphors show potential as an effective material for fingerprint detection in forensic science applications.